Enhanced and disruptive radio-frequency receivers - Prata, André Isidoro (2018)
This Ph.D. mainly addresses the reception part of a radio front end, focusing on Radio Frequency (RF) sampling architectures. These are considered to be the most promising future candidates to get better performance in terms of bandwidth and agility, following the well-known Software-Defined Radio (SDR) concept. The study considers the usage of an RF receiver in a standalone operation, i.e., used for receiving unknown data at the antenna, and when used as observation path for Power Amplifier (PA) linearization via Digital Predistortion (DPD), since nowadays this represents a mandatory technique to increase overall system’s performance. Firstly, commercial available RF Analog-Digital-Converters (ADCs) are studied and characterized to understand their limitations when used in DPD scenarios. A method for characterization and digital post-compensation to improve performance is proposed and evaluated. Secondly, an innovative FPGA-based RF single-bit pulsed converter based on Pulse Width Modulation (PWM) is addressed targeting frequency agility, high analog input bandwidth, and system integration, taking profit of an FPGA-based implementation. The latter was optimized based on PWM theoretical behavior maximizing Signal-to-Noise-Ratio (SNR) and bandwidth. The optimized receiver, was afterwards evaluated in a 5G C-RAN architecture and as a feedback loop for DPD. Finally, a brief study regarding DPD feedback loops in the scope of multiantenna transmitters is presented. This Ph.D. contributes with several advances to the state-of-the-art of SDR receiver, and to the so-called SDR DPD concept.